Pan Africa business simulation games: The ITIS case study - Cossa, G.; Alturas, B.; Pinto, A. C.; Roque, L. G. (Simulation and Gaming for Social and Environmental Transitions: Proceedings of the 54th Conference of the International Simulation and Gaming Association, 2023)
Economists have demonstrated a positive correlation between management quality and the country's economic performance. In turn, business simulation games have shown their educational effectiveness in developing management skills crucial for African countries. However, its use is still nascent. Although they present different characteristics favorable to its implementation, for example, The African Continental Free Trade Area, the Digital Transformation Strategy Project for Africa (2020-2030), and The Pan-Africa Games Group, they also present singular characteristics such as the predominance of the informal sector, political instability, and high corruption rates. These factors influence the designing and adoption of the Pan-African Business Simulation Games Framework suitable for this specific context. This proposal aims to contribute a gaming framework to support collaborative development and appropriation by the end-users and Multi-User with content representative of their contextual diversity. The successful EVER project and Bootcamp created by the Mozambican firm ITIS, which adopted a lean startup methodology to add local content in Business Games, can inspire the Pan African Business Simulations Games - PABSG.